TRANSFORMING TRAINING INTO PRACTICE: TEACHER PROFESSIONAL DEVELOPMENT PARTICIPANTS’ CLASSROOM PRACTICE IN APPLYING THEMATIC LEARNING FOR TEACHING ENVIRONMENTAL ISSUES - Marisa Christina Tapilouw; Harry Firman; Sri Redjeki; Didi Teguh Chandra (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2019)
Teacher Professional development or TPD is a program that develops teachers’ competency to teach. This study observed how teachers who previously completed the TPD program applied thematic learning for teaching environmental issues. Classroom practice of five junior high school teachers who recently completed 32 hours of TPD was observed. Classroom observation suggested that classroom activity was varied. Their decision in designing their lesson brings about a difference in their students’ ability to understand and communicate current environmental issues. All teachers use a problem-based learning approach, which they believe to be challenging to implement before participating in TPD.